2012
DOI: 10.1097/mao.0b013e31825e799f
|View full text |Cite
|
Sign up to set email alerts
|

Extra Benefit of a Second Cochlear Implant With Respect to Health-Related Quality of Life and Tinnitus

Abstract: The present study provides evidence that the second CI leads to further increase in quality of life and reduction of tinnitus annoyance in addition to improvement of auditory abilities as compared with the first CI. Patients with bilateral CIs benefit from additional positive effects in all these fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 36 publications
9
42
2
6
Order By: Relevance
“…Overall, the tested subjects performed well in the speech in noise experiments. We observed similar speech reception thresholds (average T standard deviation, 0.6 T 1.6 dB) in the S 0 N 0 situation as in a previous study (16) with 28 unilateral CI users (0.7 T 1.8 dB). The standard deviation of the test-retest differences is slightly higher than reported in another study (T1.1 dB) (17).…”
Section: Discussionsupporting
confidence: 88%
“…Overall, the tested subjects performed well in the speech in noise experiments. We observed similar speech reception thresholds (average T standard deviation, 0.6 T 1.6 dB) in the S 0 N 0 situation as in a previous study (16) with 28 unilateral CI users (0.7 T 1.8 dB). The standard deviation of the test-retest differences is slightly higher than reported in another study (T1.1 dB) (17).…”
Section: Discussionsupporting
confidence: 88%
“…The bilateral CI could be an ultimate target of hearing rehabilitation. In fact, sustained improvement of TQ scores was observed in 40 patients subjected to sequential bilateral CI (25). …”
Section: Discussionmentioning
confidence: 98%
“…In addition, they were asked to complete psychometric questionnaires before surgery and during each consecutive appointment. The audiological tests and psychometric questionnaires used were previously described in detail (14, 25) and are presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Summerfield et al [4] have reported improved hearing-related QoL and Olze et al [5] health-related QoL in patients after sequential bilateral cochlear implantation. Moreover, patients with two CIs have less social restriction and better emotional well-being and cognition [6,7].…”
Section: Introductionmentioning
confidence: 98%